Social determinants and sexual risk behaviors within Immunodeficiency Virus cases in Solidaridad, Quintana Roo, Mexico - Chavira-Trujillo, Gabriel; Llamas Ramos, Leonardo; Jiménez Corona, Aida; Geers, Rudolf; Reyna Sevilla, Antonio; Grover Baltazar, Gabriela Alejandra; Jiménez Corona, María Eugenia (Horizonte Sanitario, 2023)
Objective: To determine the prevalence of HIV in individuals by analyzing the influence of social determinants and sexual risk behaviors, in order to estimate the crude and adjusted risks of being HIV positive in the municipality of Solidaridad, state of Quintana Roo, Mexico. Method and Materials: A cross-sectional study was conducted in the municipality of Solidaridad, Quintana Roo, Mexico. Third and fourth generation HIV rapid tests were performed. Descriptive statistics, measures of association (OR and 95 % CI) and p value were calculated for each stratum. Logistic regression models were performed to determine the risk factors associated with being HIV positive in the tests. Results: The sample consisted of 4,800 people, of whom 3,030 were men (63.12%); the mean age was 32.6 years (SD 14.96). The variables included in the multivariate model for being HIV positive are: men who have sex with men with OR=61.20, age 30-39 years OR=1.72, having anal sex OR=2.21, and as a protective factor having health service OR =0.42. Conclusions: This study confirms already known social determinants such as being male and being in economically active age and sexual practices such as: having anal sex and men with men. Being entitled to health services was shown to be the only protective factor. Keywords: Epidemiologic Factors; Sexuality; HIV; Epidemiology.